Thoracic Aorta Aneurysm Repair in a Patient with a Solitary Kidney: Hybrid Surgery as a Bailout Procedure - Bakoyiannis, Chris; Moris, Demetrios; Karaolanis, George; Patelis, Nikolaos; Schizas, Dimitrios; Georgopoulos, Sotirios; Liakakos, Theodoros (Frontiers in Surgery, 2016)
Thoracic endovascular aortic repair (TEVAR) is an emerging treatment option for thoracic aorta aneurysms (TAA). Endovascular access is a challenge. We present a novel TEVAR-technique in a patient with single kidney and a 6.4cm TAA. Attempting to place a sheath through iliac arteries was unsuccessful. The decision to proceed to hybrid-TEVAR was made. The protection of the solitary kidney was achieved through axillo-femoral bypass, followed by an end-to-side anastomosis between the aorta and a bifurcated graft. Through the graft, a stent was introduced in the thoracic aorta. With the use of contrast material, the right position of the graft was confirmed.